Decatungstate‐Mediated C(sp3)–H Heteroarylation via Radical‐Polar Crossover in Batch and Flow. Issue 33 (9th July 2021) - Wan, Ting; Capaldo, Luca; Laudadio, Gabriele; Nyuchev, Alexander V.; Rincón, Juan A.; García‐Losada, Pablo; Mateos, Carlos; Frederick, Michael O.; Nuño, Manuel; Noël, Timothy
Abstract: Photocatalytic hydrogen atom transfer is a very powerful strategy for the regioselective C(sp 3 )–H functionalization of organic molecules. Herein, we report on the unprecedented combination of decatungstate hydrogen atom transfer photocatalysis with the oxidative radical–polar crossover concept to access the direct net‐oxidative C(sp 3 )–H heteroarylation. The present methodology demonstrates a high functional group tolerance (40 examples) and is scalable when using continuous‐flow reactor technology. The developed protocol is also amenable to the late‐stage functionalization of biologically relevant molecules such as stanozolol, (−)‐ambroxide, podophyllotoxin, and dideoxyribose. Abstract : The combination of decatungstate photocatalysis with oxidative radical–polar crossover is reported. This strategy enables the C(sp 3 )–H heteroarylation under mild conditions with excellent functional group tolerance. It was also adopted to enable late‐stage functionalization of valuable compounds. Microflow technology reduced reaction times and boosted productivity of the transformation.